2019
DOI: 10.1177/0095399719833628
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Frustration: The Unintended Cultural Effect of Local Democratic Innovations

Abstract: Most research on participatory processes has stressed the positive effects that these institutions have in the relationships between public authorities and civil society. This article analyzes a more negative product that has received scant attention: participatory frustration. Departing from Hirschman’s cycles of involvement and detachment, the article shows four paths toward frustration after engaging in institutional participatory processes: (a) inflated expectations, (b) the failure of design and adjusting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
0
17
0
5
Order By: Relevance
“…Most of them agree that the ACs' influential capacity is limited, but they accept this role as it has been made clear since their creation. The appearance of "participatory frustration" (Fernández-Martínez et al, 2019) has a greater connection to unfulfilled promises than to the modest objectives of these institutions. Participants tend to appreciate that they can perform different democratic roles (Goodin & Dryzek, 2006;Jaske & Setala, 2019) and that some of them, such as agenda-setting or public debate, may be just as interesting (see also Bua, 2017) as the role of making final decisions about detailed policy solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them agree that the ACs' influential capacity is limited, but they accept this role as it has been made clear since their creation. The appearance of "participatory frustration" (Fernández-Martínez et al, 2019) has a greater connection to unfulfilled promises than to the modest objectives of these institutions. Participants tend to appreciate that they can perform different democratic roles (Goodin & Dryzek, 2006;Jaske & Setala, 2019) and that some of them, such as agenda-setting or public debate, may be just as interesting (see also Bua, 2017) as the role of making final decisions about detailed policy solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the autonomy of allied social movements and the opening of institutions to enable grassroots actors to act as a counterbalance is an important feature of a DDG regime. Failure to foster radical change through participatory processes may however generate a disaffection spiral that risks hampering the political capacity of social movements allied to the DDG administration (Fernández et al 2019). The machinery of city government is not a neutral tool and can exercise strong influence in policy implementation (John 2011).…”
Section: Between Gdd and Ddg: A Dynamic Relationshipmentioning
confidence: 99%
“…However, the fate of these institutions has always been related to their legitimacy [5,17,23], which suggests a concern for participants' satisfaction with their functioning. Previous studies have shown that this satisfaction cannot be taken for granted, and may even result in participatory frustration [24,25]. Thus, it is necessary to incorporate participants' satisfaction into the analysis, since all these aspects influence whether participants have a more or less troubling view of these participatory institutions and the role conflict plays in them.…”
Section: From Defining Characteristics To Perceptionsmentioning
confidence: 99%